ANALISA METODE IPA UNTUK MENENTUKAN KUALITAS SISTEM INFORMASI SIMPAN PINJAM PEREMPUAN - Yogi Wiyandra; Firna Yenila (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The research explain the quality of the women's savings and loan information system (SPP) at the V Koto Kampung Dalam office. The desktop-based analysis system provides some information to employees and customers about women's savings and loans (SPP). Analysis of the quality of this information system is carried out using the IPA (Importance Performance Analysis) method which involves several variables including usability variables, information quality, service quality and overall variables. This variable will explain the condition of the system that is running at UPK V Koto Kampung Dalam. Each of these variables will be included in several questions about the current system to the respondent. The data processing process in this study used 50 respondents with 22 questions involving these variables. With the analysis process involving 50 respondents, it can be stated that the IPA method is able to provide assessment results in the form of new information in the form of recommendations for the system to be developed by the agency. From the measurement results, the impact on women's savings and loans is due to the community understanding and knowing the quality of system services based on the information system used. This study was built using descriptive quantitative methods that provide results in the form of information.